The Generation of ‘The Wandering Years’ – Traveling culture in Europe and in Hungary between the World Wars - Németh, Ákos (Tudásmenedzsment, 2023)
In my article, I try to offer a comparative view of Western European and Hungarian travel literature between the World Wars. First, I examine the changes of Western traveling culture in the post-war era, then I analyze the narrato-poetic features of the travelogue, as a popular literary genre of the 1920s and 1930s. In the second chapter of my study, I introduce the Hungarian contemporaries of Waugh, Green, or Orwell. They were the generation of ‘the wandering years’, as it was called by one of them, Antal Szerb. I argue, that the main questions of the Hungarian travelers and narrative characteristics of their works not just simply resemble to the Western authors’, but they could give a relevant contribution to the contemporary European travel literature, emphasizing the integration of the thinking of Hungarian intellectuals to the European stream.